Thiol-modified activated carbon material for sensor technology - Zhexembekova, Anar; Akhmetova, Nuriya; Molkenova, Anara; Bakenov, Zhumabay; O'Hare, Danny (My University, 2017)
Abstract Activated carbon (AC) is a material of great potential in production of membranes for a construction of novel electrochemical sensors due to highly microporous structure and greater surface area per unit volume [1]. Herein we report the production of thiol-modified activated-carbon-based composite. It was obtained by treatment of ketjen black (KB) with concentrated nitric acid (69 wt.%) and further mixing with sulfur (5 wt.%) through high-energy ball milling process. The obtained composite underwent two-stage heat treatment in a tubular furnace under an atmosphere of Ar followed by 4% H2 in N2. All samples were characterized using thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FT-IR). The presence of thiol functional was validated by absorbance peaks at around 665 cm-1 and 2360 cm-1. As revealed by TGA, sulfur doped activated KB (KB/S) underwent significant mass loss (70.5%) compared with KB (0.8%), which corresponds to an increase in the effective surface area.
Keywords: Thiol-modified carbon; Sensors; Absorbance; Working electrode; Sensing electrode; Microporous membrane; Surface area